Prevalence Of Gingival Recession Among Patients Using Different Forms of Tobacco in South Indian Population- A Retrospective Study (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Gingival recession (GR) is a condition in which the gingival border is apical to the cementoenamel junction and the root is exposed to the oral environment.Tobacco use is one of the most important risk factors for the development of destructive types of periodontal disease, as well as a risk factor for GR.Aim: The aim of the present cross-sectional study was to assess the prevalence of gingival recession among patients visiting a university dental hospital setting who are using different forms of tobacco.Materials & Method: This study was conducted during the period of November 2019 to April 2020 in Saveetha Dental College and Hospitals in Chennai among patients with gingival recession who are under the usage of various forms of tobacco. The data were sorted and tabulated in Microsoft Excel and then entered in IBM SPSS software version 23 for descriptive statistics.Results And Discussion: According to the results there is a decline in tobacco users with increase in age, drastically so after the age of 50. Figure 3 shows us that there is a maximum prevalence of GR of 19.60% among the age group 40-50 years and also shows the gradual increase in the prevalence of GR with age in accordance with the number of participants belonging to each age group.There may be a higher chance of prevalence of GR among those who use both the forms of tobacco,i.e smokable and chewable than just a single form of useage.Conclusion: From this retrospective study we conclude that gingival recession is evident in patients who use various forms of tobacco with a prevalence rate of 68.40 %. Highest prevalence of gingival recession among the age groups is 19.60% of age group 40-50 years who majorly smoked and used chewable forms of tobacco.